SIMULASI JARINGAN UNTUK SISTEM DISTRIBUSI DRUPAL DENGAN GNS3 - Witriatna Kosahi; Hansen Pratama; Maryanto; Henokh Mikhael Kristiantan; Carlouis Fernando Hariyadi5 (Fakultas Teknologi Informasi Universitas Tarumanagara, 2024)
Opening an e-commerce business offers tremendous flexibility and convenience. Unlike traditional stores, an online business allows entrepreneurs to operate from anywhere at any time. The purpose of this research is to assist people who wish to start an e-commerce business without having to invest a lot of money and time in the website building. For the building of the e-commerce website in our research, we use the Drupal open-source framework and Cloud Platform as a service (PaaS). Cloud PaaS provides a dependable, effective, secure, and stable business.Then, we perform the network simulations using a virtual machine program known as GNS3. Additionally, Cloud PaaS gives users flexibility by enabling them to access it from any location and instantly expand the capacity of their server. The result of this research allows the users that is in the inside of the zone and dmz zone to access the Internet. Additionally, users from outside of the zone are able to access the http://192.168.3.3/drupal and the drupal servers